Una inscripción ibérica sobre plomo procedente del poblado de la Moleta del Remei (Alcanar, Montsià, Tarragona) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
As a result of the review of the archaeological materials from the Iberian town La Moleta del Remei, recovered during the excavations conducted between 1985 and 1997, an Iberian inscription, until now unnoticed, was found on the surface of a small piece of lead. This piece corresponds to a fragment of a bigger sheet. It presents several evidences of damages, as cuts and possible melting attempts. The inscription contains 21 signs of the northeastern Iberian system writting, distributed in three lines. The bad conservation of the object, the fragmentary state of the texts and the poor information provided for the archaeological context do not allow any precision about the possible function of the document.
Keywords: Iberian Inscription; Lead Plaque; Iberian Script; Iberian Language; Ilercavones